2017
DOI: 10.1017/s0021859617000739
|View full text |Cite
|
Sign up to set email alerts
|

Classification of confectionary sunflower genotypes based on morphological characters

Abstract: SUMMARYKnowledge of genetic diversity of confectionary sunflower can have a large impact on its use in breeding programmes. However, levels and distribution of genetic variation within the confectionary sunflower gene pool are still not adequately explored. The aim of the present paper was to describe the diversity of 68 confectionary sunflower genotypes: open-pollinated varieties, lines and hybrids. A total of 32 morphological traits were used for characterization. The Shannon & Weaver diversity index (H)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 30 publications
7
16
1
Order By: Relevance
“…Similar grouping of RHA and CMS confectionary sunflower lines was found by Hladni et al. (2017). Traits like LBLIS and LSIZ were less variable and less expressed in Rf lines, pointing to increased selection pressure and loss of variability compared with HA lines.…”
Section: Discussionsupporting
confidence: 87%
“…Similar grouping of RHA and CMS confectionary sunflower lines was found by Hladni et al. (2017). Traits like LBLIS and LSIZ were less variable and less expressed in Rf lines, pointing to increased selection pressure and loss of variability compared with HA lines.…”
Section: Discussionsupporting
confidence: 87%
“…The literature regarding change in leaf area index or leaf size with plant population is less explored; however, Ibrahim (2012) found that decreased sunflower plant population produced plants with greater leaf area. In addition, Hladni et al (2017) mentions that confectionary sunflowers typically have a larger lamina (the flat part of the leaf blade) compared to that of oilseed cultivars. The architecture of the confectionary sunflower cultivars used in our study together with a lower stand density may have resulted in a stronger relationship between AO sensor readings and oilseed sunflower.…”
Section: Resultsmentioning
confidence: 99%
“…The world production and market share of large-seed and confectionery sunflower has been increasing steadily for the past 5 years (Hladni et al, 2017). However, there is no precise information on the sowing areas of large-seeded varieties and hybrids of sunflower in Eastern European countries 1 because the sunflower producers do not provide separate data on the share of such varieties in gross revenue of all manufactured products in statistical reports.…”
Section: Current Situation In Eastern Europe Regarding Market Demandsmentioning
confidence: 99%
“…Production of confectionery sunflower shows a steady increase due to its nutritional value and use in human nutrition (Hladni et al, 2017). It is expected that a highly productive confectionery hybrids will replace varieties, which will lead to the increase of surfaces under confectionery sunflower (Hladni, 2016).…”
Section: Present Status and Future Directions Of Confectionery Sunflomentioning
confidence: 99%